EP1107 Implementation and feasibility of a digitized self-management intervention targeting cancer patients. (1st November 2019) - Olesen, ML; Uffelmann, J; Zoffmann, V
Abstract : Introduction/Background: In Denmark, evidence-based individualized follow-up is recommended after gynecological cancer (1) in addition to medical follow-up. The recommendation includes psychosocial and self-management supportive interventions. We have developed a nurse-led self-management intervention called Guided Self-Determination Gynecological Cancer (GSD-GYN-C) (2) comprising preparatory paper reflection sheets completed by patients before an individual number of conversations with a certified nurse. In a randomized trial, we observed that GSD-GYN-C improved gynecological cancer survivors' physical quality of life after 9 months (3). A digitized version of GSD-GYN-C was sought by the women due to long transportation times. In 2016/17, we therefore collaborated with The Public Danish eHealth Portal, Sundhed.dk, to develop a digitally assisted version. When moving from a paper reflection tool and face-to-face conversations into a virtual world with a digitized reflection tool and sometimes video conversations, it is important to address how interactions may change in a real-life clinical setting and document the maturity of the digital GSD in a feasibility study. Methodology: Action research (AR) (4) was applied. From the autumn of 2018, patients have been invited to use the digital version in three departments treating oncology patients. Data has been continuously collected in terms of summary of meetings, diaries, questionnaires and interviews with patients, nurses and leaders. Results: The data collection is ongoing, six patients have received digitally assisted GSD-courses and 12 interviews have been conducted with participants. Preliminary findings include that the digitized intervention was easy and intuitive to use despite some technical barriers. The patients receive a support they otherwise would not have had. Some patients with cognitive challenges like memory loss experienced difficulties. Delivering the intervention through video conversation has been challenging. Further analysis of data will be presented at the conference. Conclusion: Our preliminary findings suggest the digitized version of GSD-GYN-C appears to be feasible in clinical practice. Disclosure: Nothing to disclose